Impact of Religiosity and Spirituality on Negative Automatic Thoughts, Depression, Anxiety, and Stress among Muslim and Christian Adolescents - Ahmed, Saad; Aziz, Fahad; Kausar, Erum (Annals of Human and Social Sciences, 2025)
The research aims to understand the relationship between religiosity, spirituality, and negative automatic thoughts, depression, anxiety, and stress among adolescents.